CGIAR Future Contributions and Climate Change Classification - Esponda Bernal, Maria Del Mar; Amahnui, George Amenchwi; Andrade López, Robert Santiago (2024)
This document encompasses the Investment Prospectus for the 32 initiatives planned for 2022-2024, categorized based on their relationship with climate change approaches.